Technological Change during the Energy Transition - Gerard van der Meijden; Sjak Smulders (Tinbergen Institute, 2014)
The energy transition from fossil fuels to alternative energy sources has important consequences for technological change and resource extraction. We examine these consequences by incorporating a non-renewable resource and an alternative energy source in a market economy model of endogenous growth through expanding varieties. During the energy transition, technological progress is non-monotonic over time: it declines initially, starts increasing when the economy approaches the regime shift, and jumps down once the resource stock is exhausted. A moment of peak-oil does no longer necessarily occur, and simultaneous use of the resource and the alternative energy source will take place if the return to innovation becomes too low.
Keywords: O30; Q32; Q42; Q56; 330; Alternative energy sources; endogenous growth; energy transition; non-renewable resources; technological change